THE CONCEPT OF PROFESSIONAL RELIABILITY IN THE CONTEXT OF TRAINING FUTURE AIR TRAFFIC CONTROLLERS - Смирнова, І. Л.; Приз, О. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In this article author studies such a definition as professional reliability of operator in different scientific studies of Ukrainian and foreign authors. Author shows importance of formation professional reliability of future air traffic controllers. There is a definition of psychologically-pedagogical problems, which hinder formation of professional reliability of future air traffic controllers